SIKLUS DALAM SISTEM INFORMASI AKUNTANSI - Atika Atika (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
An accounting information system is a component that collects, categorizes, processes, analyzes, and combines relevant financial information for decision making by external parties. The existence of a good information system will produce information according to needs. Good information is information that can be presented in a timely manner, useful and reliable. One of the important information systems in a company is an accounting information system. The purpose of this research is to find out what cycles exist in the accounting information system. The results of this study indicate that the cycle in the accounting system is very important to know in detail. The accounting information system cycle includes the income cycle, the expenditure cycle, the human resource payroll cycle, the production cycle, and the financial cycle.